2010
DOI: 10.1135/cccc2010010
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of disopyramide and its adsorptive stripping determination in pharmaceutical dosage forms and biological fluids

Abstract: Electrochemical behavior of disopyramide (DPA) and optimum conditions to its quantitative determination were investigated using voltammetric methods. Some electrochemical parameters such as diffusion coefficient, surface coverage of adsorbed molecules, electron transfer coefficient, standard rate constant and number of electrons were calculated using the results of cyclic and square-wave voltammetry. All studies were based on the quasi-reversible and adsorption-controlled electrochemical reduction signal of DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Result of concentration studies showed that an average peak current of reduction wave changed linearly with RPN concentration in the range from 1.5 to 150 nmol l -1 by obeying the calibration equation I p (nA) = 0.51[RPN] (nmol l -1 ) + 10.65 with R 2 = 0.9992. Value of R 2 is the evidence of good linearity between peak current and concentration of RPN (Table I) Limits of detection and quantitation: Limit of detection (LOD) and limit of quantitation (LOQ) values for RPN were calculated using the relations LOD = 3s/m and LOQ = 10s/m 23,24 . The abbreviation of s is the standard deviation of intercept of calibration curve and m is the slope of the related calibration curve, LOD and LOQ values were found 5.18 nmol l -1 (2.12 µg l -1 ) and 17.25 nmol l -1 (7.07 µg l -1 ), respectively.…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Result of concentration studies showed that an average peak current of reduction wave changed linearly with RPN concentration in the range from 1.5 to 150 nmol l -1 by obeying the calibration equation I p (nA) = 0.51[RPN] (nmol l -1 ) + 10.65 with R 2 = 0.9992. Value of R 2 is the evidence of good linearity between peak current and concentration of RPN (Table I) Limits of detection and quantitation: Limit of detection (LOD) and limit of quantitation (LOQ) values for RPN were calculated using the relations LOD = 3s/m and LOQ = 10s/m 23,24 . The abbreviation of s is the standard deviation of intercept of calibration curve and m is the slope of the related calibration curve, LOD and LOQ values were found 5.18 nmol l -1 (2.12 µg l -1 ) and 17.25 nmol l -1 (7.07 µg l -1 ), respectively.…”
Section: Methods Validationmentioning
confidence: 99%
“…Its remarkable sensitivity is attributed to the combination of an effective accumulation step with an advanced measurement procedures that generates an extremely favorable signal to back ground ratio. It usually involves a simple deposition step and most of the excipients used, not interfere in the subsequent determination of the drugs and there are many applications of stripping voltammetric methods [17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…The in situ plating of lead films is possible in basic and fairly alkaline media, where Pb(II) ions do not hydrolyze according to the reaction: In this study an in situ plated lead film electrode was tested using solutions containing ammonia buffer or sodium hydroxide and disopyramide (DPA). DPA is categorized as a class IA antiarrhythmic drug according to the Vanghan and Williams's classification [21]. In the first experiments an ammonia buffer was used as the supporting electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…3 , peak potential shifts to more anodic values with increasing scan rate confirming and supporting the irreversibility or quasi-reversibility of oxidation under investigation. For this kind of mechanism, the relationship between the peak potential ( E p ) and logarithm of scan rate is expressed as [15]
Figure 3 Effect of scan rate on peak parameters in BR buffer of pH 4.0 when concentration of ARP is 8 mM (inset ( a ) variation of peak potential with logarithm of scan rate, ( b ) graph of peak current vs. scan rate, ( c ) graph of logarithm of peak current vs. logarithm of scan rate, ( d ) graph of peak current vs. square root of scan rate).
…”
Section: Resultsmentioning
confidence: 99%
“…When the linear line given in Fig. 3 ( c ) is analyzed, it will be noticed that the logarithm of peak current changed linearly with the logarithm of scan rate with a slope value of 0.78 and this slope is midway between 0.5 and 1.0 for ideal diffusion controlled and adsorption-controlled charge transfer mechanism, respectively [14] , [15] , [16] , [17] , [18] . Relation between peak current and square root of scan rate is not linear at whole range but linear at relatively higher scan rates as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%